The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.2196/25106
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Considerations for Reducing Diabetes Distress and Fear of Hypoglycemia in Parents of Youth With Type 1 Diabetes During the COVID-19 Pandemic

Abstract: Type 1 diabetes management can be challenging for children and their families. To address psychosocial concerns for parents of youth with type 1 diabetes, we developed two parent-focused interventions to reduce their diabetes distress and fear of hypoglycemia. Our team conducted several of these interventions during the early stages of the COVID-19 pandemic and recognized a need to make timely adjustments to our interventions. In this viewpoint article, we describe our experience conducting these manualized tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…Певні, хоча і недостатні, дослідження в цьому напрямку вже проведені, зокрема з дітьми, хворими на ЦД1, та їх батьками [44]. Проведене в Медичному центрі Лейденського університету (Leiden University Medical Center, Нідерланди) під час карантину, пов'язаного з пандемією COVID-19, обстеження 280 хворих на ЦД1 та 155 хворих на ЦД2 встановило збільшення в них рівня стресу та тривоги [45].…”
Section: оглядиunclassified
“…Певні, хоча і недостатні, дослідження в цьому напрямку вже проведені, зокрема з дітьми, хворими на ЦД1, та їх батьками [44]. Проведене в Медичному центрі Лейденського університету (Leiden University Medical Center, Нідерланди) під час карантину, пов'язаного з пандемією COVID-19, обстеження 280 хворих на ЦД1 та 155 хворих на ЦД2 встановило збільшення в них рівня стресу та тривоги [45].…”
Section: оглядиunclassified
“…3 For parents, managing their child’s T1DM is often associated with high reported levels of stress and anxiety. 4 The COVID-19 pandemic may have amplified these stressors due to COVID-19-related job loss and financial concerns, 5 , 6 the child being at higher risk of a severe COVID-19 infection, 7 and the added burden of managing their child’s diabetes in light of new responsibilities associated with the pandemic. 5 , 6 …”
mentioning
confidence: 99%
“…A recent article reported that parents rely on the structured school schedule to facilitate adherence to their child’s T1DM management regimen, and therefore, unstructured time away from school during the pandemic may also adversely impact children’s glycemic control. 5 …”
mentioning
confidence: 99%
See 2 more Smart Citations